LEGAL CULTURES AND MEDIATION. INTERACTIONS AND EVOLUTIONS - Claudiu Ramon D. BUTCULESCU (Challenges of the Knowledge Society)
Mediation, as an alternative dispute resolution method, is closely connected with the system of legal cultures. Mediation is an important link between legal culture and the judicial system. Mediation also acts as an interface between internal legal culture and external legal culture. This paper addresses the issues regarding the links and interactions between mediation and legal cultures, as well as the effects that arise from these interactions.